Quality of Antipsychotics Prescribing in Dementia Patients in Wakefield (WF9 Area) - Bhavana Piparsania; Richard Marriott; Sapan Sunder (BJPsych Open, 2025)
Aims: This Quality Improvement Project evaluated antipsychotic prescribing for dementia patients in Wakefield (WF9), comparing local practice with NICE guidelines. NICE recommends antipsychotics for severe agitation/distress, initiated and monitored under specialist supervision for ≥12 months. NHS England data (Jan 2024) shows similar dementia diagnosis rates in Wakefield compared with the national average, but antipsychotic prescribing is ~33% higher regionally. This project investigated this.